Effect of elevated viscosity in the upper gastrointestinal tract on drug absorption in dogs - Reppas, C; G. Eleftheriou; Macheras, P.; Symillides, M; Dressman, JB (EUROPEAN JOURNAL OF PHARMACEUTICAL SCIENCES, 1998)
The objectives of these studies were, first, to determine the effect of elevated luminal viscosity on the gastrointestinal absorption of four model drugs and, second, to identify the key processes influencing drug absorption under elevated viscosity conditions. Studies were conducted in vitro and in healthy female mongrel does under fasting conditions. In the canine model, both the rate and extent of paracetamol and hydrochlorothiazide absorption were significantly decreased by the coadministration of 15 g guar gum dissolved in 500 ml normal saline. In the case of cimetidine, the rate but not extent of absorption was decreased. Owing to the high variability in the data, no statistically based conclusion could be drawn about the effects of coadministered guar gum on the oral absorption of the poorly soluble mefenamic acid. Based on the in vitro data, it appears that substantial reductions in the dissolution rate of paracetamol, hydrochlorothiazide and cimetidine account for the effects observed in vivo. It is concluded that the effect of an elevation in the intraluminal viscosity on drug absorption is greatest for highly soluble drugs, and results from a combination of a decrease in dissolution rate and gastric emptying rate. (C) 1998 Elsevier Science B.V.
Keywords: binding; canine model; cimetidine; Diffusion; Dissolution; gastrointestinal drug absorption; guar gum; hydrochlorothiazide; mefenamic acid; paracetamol; Viscosity